Wybór jako podstawowy wyróżnik stylu językowego - Ruszkowski, Marek (Stylistyka, 1998)
There are three very important distinguishing features of linguistic styles: selection, construction and transformation. The notion of selection is still regarded as arguable and amiguous. The reason for that is a limited collection of possible choices the speaker can make. It is also necessary to distinguish between the stylistic selection and unstylistic one. The first one consists of pragmatic (one chooses the element which is close to the described part of reality) and grammatical choices (one chooses an element which is consistent with grammatical rules). The stylistic selection, however, assumes that the choice is made between synonymous components (elements). Therefore, it is worth distinguishing between selection as a procedure and selection as a result of this procedure. The linguistic style is established as the result of two procedures: selection and adaptation, because a linguistic element may be selected in the process of grammatical and semantic adaptation to the other elements. Probably, the procedure of selection cannot be identically applied to all functional styles.